Comparative Management Studies - Gutterman, Alan S. (Business Expert Press, 2019)
This book begins with a brief description of the history and evolution of "management studies", continues with an overview of the scope and practice of comparative management studies, and provides examples of the research that has been done on cross-cultural transfer of management theories. In addition, the book includes materials on the search for, and analysis of, dimensions of management styles that can be used as a basis for creating models that can be used for comparison purposes.